Excessive gestational weight gain in accordance with the IOM criteria and the risk of hypertensive disorders of pregnancy: a meta-analysis - Min Ren; Hanying Li; Wei Cai; Xiulong Niu; Wenjie Ji; Zhuoli Zhang; Jianmin Niu; Xin Zhou; Yuming Li (BMC, 2018)
Abstract Background Excessive gestational weight gain (GWG) is a potential risk factor for hypertensive disorders of pregnancy (HDP). Methods We systematically reviewed three electronic databases for relevant articles published in English: PubMed, EMBASE and Web of Science. The Newcastle-Ottawa Scale was used to assess study quality. Random-effects meta-analyses were performed to supply a pooled estimation of the OR comparing the risk of HDP among healthy pregnant women with and without excessive GWG. Results The pooled estimation for the association between excessive GWG and the risk of HDPs yielded an odds ratio (OR) of 1.79 (95% CI: 1.61-1.99). A subgroup analysis showed that women who had excessive GWG were more likely to have an HDP (OR 1.82; 95% CI 1.53-2.17), preeclampsia (OR 1.92; 95% CI 1.36-2.72), or gestational hypertension (OR 1.67; 95% CI 1.43-1.95). The pooled estimation for the association between excessive GWG and the risk of HDPs among pregestational normal weight women yielded an OR of 1.57 (95% CI 1.26-1.96). A subgroup analysis showed that women who had excessive GWG were more likely to have HDP (OR 1.45; 95% CI 1.09-1.92) or gestational hypertension (OR 1.51; 95% CI 1.22-1.86). The summary ORs of pre-gestational underweight women and pre-gestational overweight and obese women were 2.17 (95% CI 1.56-3.02) and 1.32 (95% CI 1.08-1.63), respectively. Conclusions The findings of this study suggest that excessive GWG in accordance with the IOM recommendations influences the rate of HDP.